Examination of the Influence of Court Disposition Status (Under Investigation, Founded) on Pre-Intervention Assessment Results in Child Protective Services Referrals. - Donohue, Brad; Plant, Christopher P.; Barchard, Kimberly A.; Scott, Jesse; Galante, Marina (Child Welfare, 2018)
This study examined how child neglect type (i.e., exposure to illicit drugs, other neglect types) and court disposition status (under investigation, founded) influence pre-treatment assessment scores in a sample of 72 mothers referred to behavioral treatment by Child Protective Services. Mothers under investigation for exposing their children to drugs evidenced higher lie scale scores and reported significantly less child maltreatment potential, compared to mothers under investigation for other types of neglect.